A Generalized Polymer Precursor Ink Design for 3D Printing of Functional Metal Oxides - Chen, Hehao; Wang, Jizhe; Peng, Siying; Liu, Dongna; Yan, Wei; Shang, Xinggang; Zhang, Boyu; Yao, Yuan; Hui, Yue; Zhou, Nanjia (Nano-Micro Letters, 2023)
Three-dimensional-structured metal oxides have myriad applications for optoelectronic devices. Comparing to conventional lithography-based manufacturing methods which face significant challenges for 3D device architectures, additive manufacturing approaches such as direct ink writing offer convenient, on-demand manufacturing of 3D oxides with high resolutions down to sub-micrometer scales. However, the lack of a universal ink design strategy greatly limits the choices of printable oxides. Here, a universal, facile synthetic strategy is developed for direct ink writable polymer precursor inks based on metal-polymer coordination effect. Specifically, polyethyleneimine functionalized by ethylenediaminetetraacetic acid is employed as the polymer matrix for adsorbing targeted metal ions. Next, glucose is introduced as a crosslinker for endowing the polymer precursor inks with a thermosetting property required for 3D printing via the Maillard reaction. For demonstrations, binary (i.e., ZnO, CuO, In2O3, Ga2O3, TiO2, and Y2O3) and ternary metal oxides (i.e., BaTiO3 and SrTiO3) are printed into 3D architectures with sub-micrometer resolution by extruding the inks through ultrafine nozzles. Upon thermal crosslinking and pyrolysis, the 3D microarchitectures with woodpile geometries exhibit strong light-matter coupling in the mid-infrared region. The design strategy for printable inks opens a new pathway toward 3D-printed optoelectronic devices based on functional oxides. Highlights: 1 A facile and generalized design strategy of polymer precursor inks was developed for direct ink writing of metal oxide into submicron 3D architectures. 2 The Maillard reaction between polyethyleneimine and glucose endows the 3D-printed precursors with the excellent shape fidelity during high-temperature pyrolysis. 3 As-printed 3D periodic dielectric structure with woodpile geometry shows a significant light-matter effect in mid-infrared region.